Preparation method of coconut fiber derived porous carbon-sodium ion battery negative electrode material

Through the preparation of porous carbon derived from coconut fiber, the material structure collapse problem caused by the large sodium ion radius of sodium ion batteries is solved, and the high cycle stability and electrochemical performance of sodium ion batteries are improved.

CN119706839APending Publication Date: 2025-03-28LIAONING STARRY SKY SODIUM BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411942248.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The ion radius of sodium ions is large, which accelerates the collapse of material structure during ion transport, which in turn leads to poor circulation and electrochemical stability of sodium ion batteries.

Method used

Coconut fiber-derived porous carbon is used as the negative electrode material for sodium ion batteries, and prepared by hydrothermal method and chemical activation to form a biochar negative electrode material with rich mesoporous structure.

Benefits of technology

It effectively suppresses the collapse of material structure during ion transport, significantly enhances the circulation and electrochemical stability of sodium ion batteries, and has low cost, fast reaction rate, simple operation and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706839A_ABST
    Figure CN119706839A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a preparation method of a coconut fiber derived porous carbon-sodium ion battery negative electrode material, which comprises the following steps: putting coconut fibers into a high-pressure reaction kettle, adding deionized water, and then putting the high-pressure reaction kettle into a drying oven for hydrothermal reaction. Taking out a sample, washing with deionized water for multiple times, drying to obtain a precursor 1, and placing the precursor 1 in a planetary ball mill for ball milling treatment; mixing the ground sample with an activating agent, dispersing the mixture in deionized water, magnetically stirring the mixture at room temperature to obtain a precursor 2, drying the precursor 2 in a drying oven, and then transferring the precursor 2 into a crucible; from the perspective of material porosity regulation, the coconut fiber derived porous carbon-sodium ion battery negative electrode material with a rich pore structure is obtained through hydro-thermal treatment and chemical activation, and has excellent long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material. Background Art

[0002] Biomass carbon negative electrode material is a carbon material with high specific surface area, porous structure and good electrochemical performance obtained by pyrolysis and activation of biomass materials (such as plants, animals and microorganisms). As one of the hard carbon materials, it has high capacity and good cycle stability, and has broad application prospects in sodium ion batteries.

[0003] However, due to the large ionic radius of sodium ions, the material structure collapses rapidly during ion transport, causing the electrode material performance to decay sharply, leading to poor battery cycle and electrochemical stability.

[0004] Therefore, inventing a method for a simple, efficient and stable biomass carbon negative electrode material will be particularly important for future industrialization and large-scale application production. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a coconut fiber-derived porous carbon-sodium ion battery negative electrode material, which has multiple excellent characteristics such as high efficiency, rapidity, good stability, etc., effectively inhibits the phenomenon of material structure collapse during ion transmission, effectively enhances the advantages of the cycle and electrochemical stability of the sodium ion battery, and solves the problem that due to the large ion radius of sodium ions, the material structure collapse is accelerated during ion transmission, the performance of the electrode material decays sharply, and then the cycle and electrochemical stability of the battery are poor.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a coconut fiber-derived porous carbon-sodium ion battery negative electrode material, the preparation method is completed according to the following operating steps:

[0007] Step 1: Place coconut fiber in an autoclave, add deionized water, and then place the autoclave in an oven for hydrothermal reaction. After taking out the sample, wash it with deionized water several times and then dry it to obtain a precursor 1.

[0008] Step 2: Place the precursor 1 in a planetary ball mill for ball milling. Mix the ground sample with an activator and disperse them in deionized water. Stir the mixture magnetically at room temperature to obtain a precursor 2.

[0009] Step 3, the precursor 2 is dried in an oven, then transferred to a crucible, and carbonized in a nitrogen protective atmosphere device to obtain the precursor 3. After cooling to room temperature, the precursor 3 is ground, then mixed with hydrochloric acid, and washed with deionized water several times until the pH value of the filtrate reaches a neutral value, and then dried in an oven to obtain coconut fiber-derived porous carbon.

[0010] Preferably, in the step 1, 10 to 20 parts of coconut fiber and 50 to 60 parts of deionized water are added to the autoclave by weight.

[0011] Preferably, in step 1, the hydrothermal reaction temperature is 150° C. to 180° C., the hydrothermal reaction time is 10 h to 14 h, the oven drying is 60° C. to 90° C., and the oven drying time is 12 h to 14 h.

[0012] Preferably, the spheroidal graphite time in step 2 is 8 h to 12 h, and the average particle size of the sample after spheroidal graphite is 65 μm to 85 μm.

[0013] Preferably, in step 2, the activator is one of zinc chloride, potassium hydroxide and potassium carbonate, and the mass ratio of coconut fiber to activator is 1:(1-4).

[0014] Preferably, in the step 2, the sample is mixed in 20 mL to 30 mL of deionized water, and the magnetic stirring time is 1 h to 2 h.

[0015] Preferably, in step 3, the drying temperature of the precursor 2 is 100° C. to 120° C., the carbonization temperature is 550° C. to 850° C., the heating rate is 5° C. / min to 10° C. / min, and the holding time is 1 h to 2 h.

[0016] Preferably, in step three, 3-6 mol / L hydrochloric acid is used for mixing, the oven drying temperature is 80° C.-100° C., and the drying time is 12 h-14 h.

[0017] Preferably, the prepared coconut fiber-derived porous carbon material is used as a negative electrode material for a sodium ion battery, and the preparation method of the sodium ion battery is as follows: coconut fiber-derived porous carbon material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, N-methylpyrrolidone is used as a solvent to obtain a slurry, which is coated on the surface of an aluminum foil, and finally dried under vacuum conditions at 60°C to 120°C for 10h to 12h to obtain a negative electrode sheet; a sodium sheet is used as a counter electrode, glass fiber is used as a diaphragm, and NaPF6 / EC+DEC+FEC is used as an electrolyte, and a sodium ion battery is packaged in a high-purity argon glove box; the preparation method of the NaPF6 / EC+DMC+FEC electrolyte is as follows: NaPF6 is dissolved in a mixed solution of EC and DEC, and a FEC additive is added, wherein the volume ratio of EC to DMC in the mixed solution of EC and DEC is 1:1, the concentration of NaPF6 is 1mol / L, and the mass fraction of FEC is 2%.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. This method has many excellent characteristics in the preparation of materials, such as high efficiency, rapidity, simplicity, etc. It overcomes the problem of electrode material collapse caused by the large ion radius of sodium ions, prepares biochar negative electrodes, and uses coconut fiber to prepare target materials; the electrode materials have strong cycle stability and high surface area, suitable for large-scale production. This method has the advantages of low cost, simplicity and high efficiency, energy saving and environmental protection, and high product purity.

[0020] 2. The preparation method of the coconut fiber-derived porous carbon negative electrode material uses a hydrothermal method and chemical activation to prepare the material. The method has low cost, fast reaction rate, simple operation, mild and easy control, energy saving and environmental protection, high product purity and good morphology; and the prepared product biochar negative electrode material presents a rich mesoporous structure, strong cycle stability, high purity, low manufacturing cost, and significantly increased specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a surface morphology of the coconut fiber-derived porous carbon material prepared in Example 1 of the present invention under a scanning electron microscope;

[0022] Figure 2 The XRD pattern of the coconut fiber-derived porous carbon material prepared in Example 1 of the present invention;

[0023] Figure 3 This is a test graph of the charge-discharge cycle performance of the coconut fiber-derived porous carbon material prepared in Example 1 of the present invention at room temperature at a current density of 50 mA / g;

[0024] Figure 4This is a test graph of the long cycle charge-discharge cycle performance of the coconut fiber-derived porous carbon material prepared in Example 1 of the present invention at room temperature at a current density of 100 mA / g;

[0025] Figure 5 This is a rate performance test diagram of the coconut fiber-derived porous carbon material prepared in Example 1 of the present invention at room temperature at different current densities. DETAILED DESCRIPTION

[0026] See also Figure 1-Figure 5 , a method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material, the preparation method is completed according to the following steps:

[0027] Step 1: Place coconut fiber in an autoclave, add deionized water, and then place the autoclave in an oven for hydrothermal reaction. After taking out the sample, wash it with deionized water several times and then dry it to obtain a precursor 1.

[0028] Step 2: Place the precursor 1 in a planetary ball mill for ball milling. Mix the ground sample with an activator and disperse them in deionized water. Stir the mixture magnetically at room temperature to obtain a precursor 2.

[0029] Step 3, the precursor 2 is dried in an oven, then transferred to a crucible, and carbonized in a nitrogen protective atmosphere device to obtain the precursor 3. After cooling to room temperature, the precursor 3 is ground, then mixed with hydrochloric acid, and washed with deionized water several times until the pH value of the filtrate reaches a neutral value, and then dried in an oven to obtain coconut fiber-derived porous carbon.

[0030] In step 1, 10 to 20 parts of coconut fiber and 50 to 60 parts of deionized water are added to the autoclave by weight.

[0031] In step 1, the hydrothermal reaction temperature is 150° C. to 180° C., the hydrothermal reaction time is 10 h to 14 h, the oven drying temperature is 60° C. to 90° C., and the oven drying time is 12 h to 14 h.

[0032] In step 2, the spheroidal graphitization time is 8h to 12h, and the average particle size of the sample after spheroidal graphitization is 65μm to 85μm.

[0033] In step 2, the activator is one of zinc chloride, potassium hydroxide and potassium carbonate, and the mass ratio of coconut fiber to the activator is 1:(1-4).

[0034] In step 2, the sample is mixed in 20 mL to 30 mL of deionized water, and the magnetic stirring time is 1 h to 2 h.

[0035] In step 3, the drying temperature of the precursor 2 is 100° C. to 120° C., the carbonization temperature is 550° C. to 850° C., the heating rate is 5° C. / min to 10° C. / min, and the holding time is 1 h to 2 h.

[0036] In step 3, 3-6 mol / L hydrochloric acid is used for mixing, the oven drying temperature is 80° C.-100° C., and the drying time is 12 h-14 h.

[0037] The prepared coconut fiber-derived porous carbon material is used as a negative electrode material for a sodium ion battery. The preparation method of the sodium ion battery is as follows: the coconut fiber-derived porous carbon material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, N-methylpyrrolidone is used as a solvent to prepare a slurry, which is coated on the surface of an aluminum foil, and finally dried under a vacuum condition of 60°C to 120°C for 10h to 12h to obtain a negative electrode sheet; a sodium sheet is used as a counter electrode, glass fiber is used as a diaphragm, and NaPF6 / EC+DEC+FEC is used as an electrolyte, and the sodium ion battery is packaged in a high-purity argon glove box; the preparation method of the NaPF6 / EC+DMC+FEC electrolyte is as follows: NaPF6 is dissolved in a mixed solution of EC and DEC, and a FEC additive is added, wherein the volume ratio of EC to DMC in the mixed solution of EC and DEC is 1:1, the concentration of NaPF6 is 1mol / L, and the mass fraction of FEC is 2%.

[0038] Example 1: A method for preparing a coconut fiber-derived porous carbon-sodium ion battery negative electrode material, using coconut fiber and zinc chloride as raw materials, using a hydrothermal method and chemical activation, comprising the following steps:

[0039] Step 1: 15 g of coconut fiber was placed in an 80 mL polytetrafluoroethylene liner, 60 mL of deionized water was added, and the mixture was transferred to an autoclave. The autoclave was then placed in an oven at 180°C for 10 h for hydrothermal reaction. After the sample was taken out, it was washed several times with deionized water and then dried to obtain precursor 1.

[0040] Step 2: Precursor 1 is placed in a ball mill and ball-milled to an average particle size of 75 μm. 2.4 g of the ground sample is mixed with zinc chloride at a ratio of 1:1 (mass ratio) and dispersed in 20 ml of deionized water. The mixture is magnetically stirred at ambient temperature for 2 h to obtain precursor 2;

[0041] Step 3: Precursor 2 was dried in an oven at 105°C for 12 hours, then transferred to a 10 ml crucible, and pyrolyzed at 850°C for 2 hours at a heating rate of 10°C / min in a tube furnace under vacuum. After cooling to room temperature, the activated carbon was ground, mixed with 6 mol / L hydrochloric acid, and washed several times with deionized water until the pH value of the filtrate reached a neutral value. Finally, the target product was obtained by drying at 90°C for 12 hours.

[0042] like Figure 1 As shown in the SEM image, a large number of defect structures are generated on the surface of the sample prepared in Example 1, presenting a hierarchical porous structure. This pore size structure will greatly promote electrolyte penetration and sodium ion diffusion. In addition, the rich pore size distribution can improve the electrochemical performance of the material, accelerate the reaction rate and enhance the cycle stability.

[0043] like Figure 2 As shown, the XRD pattern of the sample prepared in Example 1 shows two broad diffraction peaks at 23.5° and 43°, corresponding to the (002) and (100) diffraction planes, indicating the characteristics of disordered carbon with abundant carbon plane defects, which is beneficial to the storage of sodium ions.

[0044] like Figure 3 As shown, after the sample of Example 1 was made into a pole piece and assembled into a sodium ion battery, an electrochemical test was performed, and the test voltage range was 0 to 2.00 V (vsNa + / Na), at a current density of 50mA / g, the initial reversible capacity is 119.8mAh / g,

[0045] After 200 cycles, the reversible capacity is 113.8 mAh / g, and the capacity retention rate is as high as 95%, showing excellent cycle stability.

[0046] like Figure 4 As shown, in order to further test the long cycle stability of the sample electrode material prepared in Example 1, the voltage range is 0 to 2.00 V (vsNa + / Na), tested at a current density of 100mA / g, the initial reversible capacity was 97.3mAh / g. After 1000 long cycles, the reversible capacity was 86mAh / g, and the capacity retention rate was as high as 88.4%, showing excellent long-cycle stability.

[0047] like Figure 5 As shown, the electrode material of the sample in Example 1 has a good capacity retention rate at different current densities and exhibits good rate performance.

[0048] Example 2: A method for preparing a coconut fiber-derived porous carbon-sodium ion battery negative electrode material, using coconut fiber and potassium hydroxide as raw materials, using a hydrothermal method and chemical activation, comprising the following steps:

[0049] Step 1: 15 g of coconut fiber was placed in an 80 mL polytetrafluoroethylene liner, 60 mL of deionized water was added, and the mixture was transferred to an autoclave. The autoclave was then placed in an oven at 180°C for 10 h for hydrothermal reaction. After the sample was taken out, it was washed several times with deionized water and then dried to obtain precursor 1.

[0050] Step 2: Precursor 1 was placed in a ball mill and ball-milled to an average particle size of 75 μm. 2.4 g of the ground sample was mixed with potassium hydroxide at a ratio of 1:1 (mass ratio) and dispersed in 20 ml of deionized water. The mixture was magnetically stirred at ambient temperature for 2 h to obtain precursor 2.

[0051] Step 3: Precursor 2 was dried in an oven at 105°C for 12 hours, then transferred to a 10 ml crucible, and pyrolyzed at 850°C for 2 hours at a heating rate of 10°C / min in a tube furnace under vacuum. After cooling to room temperature, the activated carbon was ground, mixed with 6 mol / L hydrochloric acid, and washed several times with deionized water until the pH value of the filtrate reached a neutral value. Finally, the target product was obtained by drying at 90°C for 12 hours.

[0052] The method for preparing highly stable coconut fiber-derived porous carbon negative electrode materials by chemical activation has many excellent characteristics in the preparation of materials, such as high efficiency, rapidity, simplicity, etc. It overcomes the problem of electrode material structure collapse caused by excessive sodium ion ion radius, prepares biomass carbon negative electrode materials, and uses zinc chloride as an activator to chemically activate the materials; the biomass carbon negative electrode materials have high cycle stability and provide stable and rapid ion channels when sodium ions undergo diffusion reactions. The method has the advantages of low cost, fast reaction rate, mild reaction and easy control, energy saving and environmental protection, high product purity and novel morphology, and solves the problem of energy density drop caused by structural collapse of existing negative electrode materials during the cycle.

[0053] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material, characterized in that: The preparation method is completed according to the following steps: Step 1: Place coconut fiber in an autoclave, add deionized water, and then place the autoclave in an oven for hydrothermal reaction. After taking out the sample, wash it with deionized water several times and then dry it to obtain a precursor 1. Step 2: Place the precursor 1 in a planetary ball mill for ball milling. Mix the ground sample with an activator and disperse them in deionized water. Stir the mixture magnetically at room temperature to obtain a precursor 2. Step 3, the precursor 2 is dried in an oven, then transferred to a crucible, and carbonized in a nitrogen protective atmosphere device to obtain the precursor 3. After cooling to room temperature, the precursor 3 is ground, then mixed with hydrochloric acid, and washed with deionized water several times until the pH value of the filtrate reaches a neutral value, and then dried in an oven to obtain coconut fiber-derived porous carbon.

2. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 1, 10 to 20 parts of coconut fiber and 50 to 60 parts of deionized water are added to the autoclave by weight.

3. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 1, the hydrothermal reaction temperature is 150° C. to 180° C., the hydrothermal reaction time is 10 h to 14 h, the oven drying temperature is 60° C. to 90° C., and the oven drying time is 12 h to 14 h.

4. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the spheroidal graphitization time is 8h to 12h, and the average particle size of the sample after spheroidal graphitization is 65μm to 85μm.

5. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the activator is one of zinc chloride, potassium hydroxide and potassium carbonate, and the mass ratio of coconut fiber to the activator is 1:(1-4).

6. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the sample is mixed in 20 mL to 30 mL of deionized water, and the magnetic stirring time is 1 h to 2 h.

7. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 3, the drying temperature of the precursor 2 is 100° C. to 120° C., the carbonization temperature is 550° C. to 850° C., the heating rate is 5° C. / min to 10° C. / min, and the holding time is 1 h to 2 h.

8. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: In step 3, 3-6 mol / L hydrochloric acid is used for mixing, the oven drying temperature is 80° C.-100° C., and the drying time is 12 h-14 h.

9. The method for preparing a coconut fiber derived porous carbon-sodium ion battery negative electrode material according to claim 1, characterized in that: The prepared coconut fiber-derived porous carbon material is used as a negative electrode material for a sodium ion battery. The preparation method of the sodium ion battery is as follows: the coconut fiber-derived porous carbon material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 7:2:1, N-methylpyrrolidone is used as a solvent to prepare a slurry, which is coated on the surface of an aluminum foil, and finally dried under a vacuum condition of 60°C to 120°C for 10h to 12h to obtain a negative electrode sheet; a sodium sheet is used as a counter electrode, glass fiber is used as a diaphragm, and NaPF6 / EC+DEC+FEC is used as an electrolyte, and the sodium ion battery is packaged in a high-purity argon glove box; the preparation method of the NaPF6 / EC+DMC+FEC electrolyte is as follows: NaPF6 is dissolved in a mixed solution of EC and DEC, and a FEC additive is added, wherein the volume ratio of EC to DMC in the mixed solution of EC and DEC is 1:1, the concentration of NaPF6 is 1mol / L, and the mass fraction of FEC is 2%.